Enhancing Grade 12 Students’ Science Process Skills through a Culturally Responsive Instructional Framework in Physics - Gecain, Julieta (Journal of Cultural Analysis and Social Change, 2025)
This study examined the level of performance of Grade 12 students in various science process skills—observing, classifying, measuring, communicating, inferring, predicting, defining operationally, formulating hypotheses, interpreting data, controlling variables, and experimenting—using a culturally contextualized instructional framework in Physics at Tuburan National High School. The research focused on students’ pretest and posttest scores in competencies related to applying the relationship R=VIR = \V{I}R=IV (Ohm’s Law) and solving related problems, while also exploring how contextualized and meaningful learning experiences may influence their engagement and skill development. Seventy students participated in the study through a descriptive design employing a questionnaire technique. Statistical tools such as weighted mean, chi-square, coefficient of contingency, and t-test were used to analyze the data. Findings revealed that students initially demonstrated a “Needs Improvement” level in both Ohm’s Law competencies. However, significant gains were observed in their posttest scores after the implementation of the instructional framework. Beyond academic improvement, the integration of familiar cultural contexts and community-based examples made Physics more accessible and relevant to learners, supporting their development as confident and critical thinkers. The results highlight the potential of culturally responsive instructional practices not only to strengthen science process skills but also to promote equitable participation and meaningful learning in Physics classrooms. The study recommends the continued use and expansion of this instructional framework in Grade 12 Physics classes at Tuburan National High School.